Genome-wide analysis identifies molecular systems and 149 genetic loci associated with income - W. David Hill (Nature Portfolio, 2019)
Household income is used as a marker of socioeconomic position, a trait that is associated with better physical and mental health. Here, Hill et al. report a genome-wide association study for household income in the UK and explore its relationship with intelligence in post-GWAS analyses including Mendelian randomization.